Mathematical methods for engineers and physicists - Mukhopadhyay, Asok Kumar
Mathematical methods for engineers and physicists / Mukhopadhyay, Asok Kumar. -- Kolkata: S. Ratan & Co. 510 M954e2 2nd ed. No. of Copies : 1